Legal Protection for Online Ojek Drivers Who are Victims of Fictitious Order - Wahyudi, Eko; Darmawan, Didit; Hardyansah, Rommy (Bulletin of Science, Technology and Society, 2023)
This study explores the legal protection available to online ojek drivers in Indonesia who fall victim to fictitious orders, a prevalent issue that impacts their financial stability and emotional well-being. The current partnership model between drivers and application companies limits drivers' legal protections, making them vulnerable without access to compensation or adequate support in reporting incidents. Through a normative juridical approach, the research evaluates existing regulations, identifies barriers faced by drivers in seeking justice, and emphasizes the roles of both the government and app companies in enhancing protections. Key recommendations include establishing clearer compensation mechanisms, improving reporting systems, strengthening legal frameworks, and utilizing advanced technology for fraud detection. Ultimately, the study calls for collaborative efforts to create a safer and fairer work environment for drivers in the gig economy.